Of Matriarchs, Slaves and Prophetesses: Women in Medieval Translations of the Bible - Marti, Melisa (Revista Melibea, 2024)
This work aims to trace the various ways of translating the female roles of the Bible in the earliest renditions into Castilian and to comparatively analyze lexical choices, taking into account the historical, cultural, doctrinal, social, and linguistic aspects that determined them. The starting point will be a corpus composed of two texts that translate, gloss, and amplify the biblical narratives, La fazienda de Ultramar and the General Estoria; and, on the other hand, the first proper translations, gathered in the Escurialense corpus of vernacular Bibles. We will focus on the analysis of the construction of pious, challenging, contemplative, and threatening female figures in the biblical text, in order to evaluate how these behavioral models were transferred into Castilian during the emergence of literature in this language. Finally, we will attempt to reconstruct some of the philosophical-doctrinal debates of the 13th and 14th centuries concerning the female characters of the Bible, as well as the historical-cultural framework in which biblical renditions circulated, to understand the scope and limitations of translation practices in the nascent Castilian literature.